2016
DOI: 10.1037/npe0000055
|View full text |Cite
|
Sign up to set email alerts
|

The putative chemosignal androstadienone makes women more generous.

Abstract: Putative human chemosignals have been shown to influence mood states and emotional processing, but the connection between these effects and higher-order cognitive processing is not well established. This study utilized an economic game (Dictator Game) to test whether androstadienone (AND), an odorous compound derived from testosterone, impacts on altruistic behavior. We predicted that the female participants would act more generously in the AND condition, exhibiting a significant interaction effect between gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
0
11
2
Order By: Relevance
“…Another possibility is that, beyond mate selection, androstenes plays a role in more general aspects of social cognition, such as person perception. Behavioral evidence supports this view, as indicated by reports of increased generosity in female, but not male, participants (Perrotta et al, 2016), or increased cooperation in male participants (Huoviala and Rantala, 2013) following exposure to androstadienone during economic games (i.e., dictator game: Kahneman et al, 1986). More directly related to face processing, exposure to androstadienone fastens reaction speed toward schematic angry faces compared to happy faces (Frey et al, 2012), but also increases the judgment of dominance in faces (Banner and Shamay-tsoory, 2018), and triggers gaze avoidance (Banner et al, 2019) in men with high social anxiety.…”
Section: General Social Cognitionmentioning
confidence: 81%
“…Another possibility is that, beyond mate selection, androstenes plays a role in more general aspects of social cognition, such as person perception. Behavioral evidence supports this view, as indicated by reports of increased generosity in female, but not male, participants (Perrotta et al, 2016), or increased cooperation in male participants (Huoviala and Rantala, 2013) following exposure to androstadienone during economic games (i.e., dictator game: Kahneman et al, 1986). More directly related to face processing, exposure to androstadienone fastens reaction speed toward schematic angry faces compared to happy faces (Frey et al, 2012), but also increases the judgment of dominance in faces (Banner and Shamay-tsoory, 2018), and triggers gaze avoidance (Banner et al, 2019) in men with high social anxiety.…”
Section: General Social Cognitionmentioning
confidence: 81%
“…Also, body odorants’ presentation in mixtures corresponding to more realistic contexts should be favored, ideally (e.g., embedded in a body odor basis, constituted by either an artificial mixture of compounds or obtained by pooling samples from many donors). Testing the effect of body odorants in real (or closer to real) social interactions (Ferdenzi et al, 2016b), for example, using economic games (Huoviala & Rantala, 2013; Perrotta et al, 2016; Tognetti et al, 2022) would help increase the ecological validity of the research in this field. More generally, more research effort is needed to identify other behaviorally relevant chemical compounds (to date, body odor knowledge rests almost only upon malodor compounds and androstenes).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, cooperative behaviours and facial and vocal characteristics have been discussed to be associated in men through a pleiotropic effect of testosterone levels (O’Connor & Barclay, 2017; Stirrat & Perrett, ; Tognetti et al, 2013, 2019). Although the composition of human body odours is influenced by androgens and although several studies showed that androstadienone, a chemical compound derived from testosterone, influence an individual's decision to cooperate or not (Banner & Shamay‐Tsoory, 2018; Huoviala & Rantala, 2013; Perrotta et al, 2016), whether natural body odours are a valid cue of cooperative behaviour has never been tested so far in humans. This study fills this gap by investigating whether body odours represent a cue to men's cooperative behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical compounds involved in the detection of cooperative behaviours remain to be determined. Compounds derived from androgens could be involved (Banner & Shamay‐Tsoory, 2018; Huoviala & Rantala, 2013; Perrotta et al, 2016) and future studies should investigate whether the composition of body odours between cooperative and non‐cooperative men varies in terms of chemical compounds derived from androgens. In addition to the possibility that body odours represent a cue of an individual's cooperative tendencies (such as high versus low cooperative individuals), body odours may also represent a cue of the cooperative behaviour itself (Gerber et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation